Behavior Physiology of Workplace Bullying and It’s Role to Job Satisfaction and Psychologycal Distress among Workers at Water Supply Company - Wulandari Putu Diana; Purnawati Susy; Prihastini Komang Angga; Gandari Ni Komang Matalia (SHS Web of Conferences, 2024)
Individuals strive to fulfill their essential needs by working. Every company has different work environment. The work environment tends to have impact on each individual. One of the key issues that usually occur at workplace is bullying. Workplace bullying can happen to anyone while both bullies and their victims may experience psychological effects from bullying. This study aims to see the effect of workplace bullying on job satisfaction and psychological distress among water supply company employees. This research design is quantitative using cross sectional design. The results showed that the psychological distress variable played a significant role in workplace bullying (p. <0.05). However, the job satisfaction variable does not contribute to workplace bullying (p. > 0.05). The serotonin trasporter-linked promoter region (5-HTTLPR) polymorphism of the SLC6A4 gene consists of an insertion/deletion that creates a short (S) 14 repeat or a long (L) 16 repeat allele. Genotype profile on one’s serotonergic system is correlated by their dominance in the community. Individuals with allele LL type is more likely become bullies when they are encouraged by the environment. In contrast, individuals with SS allele type with in a characteristic of low transcription activity at transporter serotonin gene tend to become bullying victims in their workplace due to they more vulnerable to stress. Employee with amygdala which easily triggered and intimidated by the dominant individuals, more likely to experience workplace bullying. Those employee who work in supportive workplace show higher job satisfaction and they are not distress psychologically.